2022
DOI: 10.3390/plants11192569
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evaluation of In Vitro Micropropagated and Regenerated Plants of Cannabis sativa L. Using SSR Molecular Markers

Abstract: Simple sequence repeat (SSR) markers were used to evaluate the genetic stability of the acclimatized micropropagated and regenerated plants of a high cannabidiol (H-CBD) and a high cannabigerol (H-CBG) variety of Cannabis sativa L. Shoot regeneration and proliferation were achieved by culturing calli in Murashige and Skoog basal medium (MS) supplemented with several concentrations of 6-benzyladenine (BA) or thidiazuron (TDZ). Calli derived mostly from stem explants, rather than leaves, cultured on MS supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…Moreover, SSR markers are prone to have "null alleles", i.e., no amplification of the intended PCR product, due to the mutation that can occur in the primer annealing sites, which may lead to errors in scoring. SSR markers are considered genetically stable because, when used, they did not reveal any polymorphism, or only a very low level of it, between the original plants and the regenerants [81][82][83].…”
Section: Variation At Dna Levelmentioning
confidence: 99%
“…Moreover, SSR markers are prone to have "null alleles", i.e., no amplification of the intended PCR product, due to the mutation that can occur in the primer annealing sites, which may lead to errors in scoring. SSR markers are considered genetically stable because, when used, they did not reveal any polymorphism, or only a very low level of it, between the original plants and the regenerants [81][82][83].…”
Section: Variation At Dna Levelmentioning
confidence: 99%
“…Contrarily, when using random amplified polymorphic DNA (RAPD), inter-simple sequence repeat (ISSR), and start codon targeted (SCoT) marker techniques, polymorphisms were detected among in vitro-induced cultures of Jerusalem artichoke by Abdalla et al [14]. Ioannidis et al [47] found that SSR markers could not effectively detect all genetic variability in the micropropagated plants of Cannabis sativa because of its large genome size. Therefore, more molecular markers and more primers should be adopted to obtain more molecular information about regenerated plants in the future.…”
Section: Genetic Stability Assessment Of In Vitro-regenerated Plantsmentioning
confidence: 99%
“…Other types of markers have also been shown to be useful; autosomal microsatellite markers and markers based on mitochondrial and chloroplast DNA. SSR’s have been used to differentiate between samples ( Soler et al., 2016 ; Dufresnes et al., 2017 ; Houston et al., 2017 ; Soler et al., 2017 ; Houston et al., 2018 ; de Oliveira Pereira Ribeiro et al., 2020 ; Ioannidis et al., 2022b ). It seems that a limited number of markers, from 6 to 13, is enough, not only to sort Cannabis from hop, but to individualize and differentiate between types (drug versus hemp) and to say something about geographic origin ( Houston et al., 2017 ; de Oliveira Pereira Ribeiro et al., 2020 ).…”
Section: Breeding Genetic Diversity and Genetic Markersmentioning
confidence: 99%